The Moderating Effect of Organizational Structure and Quality Practices on Absortive Capacity, Technology Compatibility and Technology Transfer Relationship - Sarina, Muhamad Noor (2010)
Technology transfer is one of the channels to upgrade development and spur growth. Many factors contributed to the performance of the transferred technology, yet few attempts were made to determine firms’ absorption capacity and technology compatibility towards the transferred technology. This study was conducted on the Electronics and Electrical firms in Malaysia to understand the performance of the transferred technology. The objectives were to determine the relationship between firms’ absorptive capacity and technology compatibility in technology transfer performance. In addition, the study also attempted to determine the moderating role of organizational size and structure and its quality practices in the absorptive capacity,technology compatibility and technology transfer performance relationship. The study used survey method. Data was analyzed using Pearson correlation and multiple regression analysis. The findings showed that absorptive capacity dimensions and technology compatibility dimension have several significant relationships with technology transfer performance. Moreover, among organizational structure, size and quality practices, few act as moderators in the relationship between absorptive capacity, technology compatibility and technology transfer performance. Finally, a post-hoc test was conducted to determine the type of moderators involved in this study. The result of this study contributed to knowledge as it discovered additional dimension of absorptive capacity that was also important in influencing the relationship of absorptive capacity,technology compatibility and technology transfer performance relationship.